A Note on the p-Laplacian Equation with Singular Coefficients (Journal of Partial Differential Equations, 2000)
We consider the solvability of the Dirichlet problem in a unit n-ball for the p-Laplacian equation with singular coefficients which are singular not only as |x| tends to 1 but also as |x| tends to 0. The existence and regularity of positive radial solutions are proved under some conditions related to parameters p, r, λ and q.